2021
DOI: 10.1080/21655979.2021.1973220
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of the prognostic and immunological role of β-actin (ACTB) in human cancers

Abstract: Beta-actin (ACTB), a highly conserved cytoskeleton structural protein, has been regarded as a common housekeep gene and used as a reference gene for years. However, accumulating evidence indicates that ACTB is abnormally expressed in multiple cancers and hence changes the cytoskeleton to affect the invasiveness and metastasis of tumors. This study aimed to investigate the function and clinical significance of ACTB in pan-cancer. The role of ACTB for prognosis and immune regulation across 33 tumors was explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…7) indicates that four of them are found associated with breast cancer, including ACTB, TMSB10, PABPC1 and ACTG1 . Study finds differential ACTB expression in breast cancer is associated with metastasis and drug resistance in breast cancer [30]. TMSB10 was upregulated in breast cancer tissues and its overexpression promotes invasion, proliferation and migration of breast cancer cells [31].…”
Section: Resultsmentioning
confidence: 99%
“…7) indicates that four of them are found associated with breast cancer, including ACTB, TMSB10, PABPC1 and ACTG1 . Study finds differential ACTB expression in breast cancer is associated with metastasis and drug resistance in breast cancer [30]. TMSB10 was upregulated in breast cancer tissues and its overexpression promotes invasion, proliferation and migration of breast cancer cells [31].…”
Section: Resultsmentioning
confidence: 99%
“…However, the emerging evidence suggests that ACTB expresses unstably and plays a key role in a variety of human diseases, particularly cancer [ 37 ]. Previous studies showed that the mRNA level of ACTB was down-regulated in esophageal cancer, colon cancer, and LUSC compared to normal tissues [ 38 , 39 ]. The same is also true for ITGB1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, some other studies found the opposite results, suggesting that ACTB was up-regulated in some cancers, such as esophageal cancer (ES) and NSCLC (not typed) compared to normal samples [ 42 , 43 ], and a study showed that up-regulated ACTB was associated with poor prognosis in LUAD [ 39 ]. These studies did not distinguish between LUAD and LUSC.…”
Section: Resultsmentioning
confidence: 99%
“…Three of six 5’- ACTB HFGs resulted in no protein alterations, while the remaining three altered N-termini; ACTB-KLF2 had an ORF without a start codon (Fig.S1). Five 3’- ACTB HFGs encoded intact β-actin; PTMA-ACTB,ELMO1-ACTB, KLF2-ACTB, TPM4-ACTB , and LFNG - ACTB encoded β-actin-involved hybrid proteins; TNRC18-ACTB and OAZ1-ACTB coded for truncated β-actin (Fig.S2), which explained why ACTB , a housekeeping gene, was abnormally expressed in cancer 27 . DDX5-CHD2, DDX5-EEF1A1, DDX5-HNRNPH3 , and DDX5-UBB encoded intact proteins, while DDX5-ATP6V0C , DDX5 -GNAS, DDX5-HNRNPU , and DDX5-SF1 produced truncated proteins (Fig.S3), which were from 43 to 702 aa shorter than their parental counterparts.…”
Section: Fig1mentioning
confidence: 99%